2001
DOI: 10.1046/j.1365-2648.2001.01768.x
|View full text |Cite
|
Sign up to set email alerts
|

Technology and humane nursing care: (ir)reconcilable or invented difference?

Abstract: The paper concludes by asking whether the commonplace appeal to resolve tensions between humane care and technology has erroneously highlighted technology as the reason for impersonal care, and encourages re-examination of the relationship(s) between technology, humane care and nursing practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
143
1
7

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(157 citation statements)
references
References 63 publications
(85 reference statements)
6
143
1
7
Order By: Relevance
“…In contrast, it has been shown that a technologically advanced caring environment may contribute to objectification of patients and nursing care, which may deprive patients of dignified subjectivity and separate nurses from their mission to care. A symbolic relationship between the technological environment and caring has previously been identified in acute settings [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, it has been shown that a technologically advanced caring environment may contribute to objectification of patients and nursing care, which may deprive patients of dignified subjectivity and separate nurses from their mission to care. A symbolic relationship between the technological environment and caring has previously been identified in acute settings [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is not technology itself that produces dehumanization, depersonalization, but the way individual technologies operate in the user's specific contexts (17) .…”
Section: Discussionmentioning
confidence: 99%
“…Although all nurses might not agree with this proposition, the parallels to be drawn within radiography are clear to see, however it could be argued that within radiography, technological competence is not so much a desirable skill, as an essential one. Like nursing, (Sandelowski, 2001) if radiographic technology is still naively perceived, even within radiography research, as an automated application of only hard technology, any attempt to define the role of the radiographer reduces the professional to merely performing a manual task, with the mindless application of medical science delivered on orders from physicians.…”
Section: Hard Technologymentioning
confidence: 99%
“…This continued polarisation might, it is suggested (Barnard and Sandelowski, 2001), comprise a discourse that is to the benefit of maintaining a distinctive professional identity to the detriment of patient care. It appears therefore that it may be in the interests of health care professionals to maintain the perceived Chapter 2 boundary.…”
Section: Soft Technological Determinismmentioning
confidence: 99%
See 1 more Smart Citation